2013
DOI: 10.1080/13691058.2012.760206
|View full text |Cite
|
Sign up to set email alerts
|

‘We do the impossible’: women overcoming barriers to cervical cancer screening in rural Honduras – a positive deviance analysis

Abstract: Cervical cancer is the leading cause of cancer death for women in Honduras, and sexual behaviour and low screening uptake are two major factors contributing to high rates of morbidity and mortality. A qualitative study was conducted to investigate barriers that prevent rural Honduran women from engaging in screening and ways that women overcome those barriers. This study examined examples of positive deviance, or individuals engaging in the uncommon but beneficial practise of screening. Amor por sí misma (self… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 31 publications
0
20
1
Order By: Relevance
“…In the Nepali context, illiteracy, inadequate access to health care, and a trend toward accessing health care for curative rather than preventive purposes could explain the low uptake of cervical smear testing [8,19]. Other studies [20,21] have also shown that support from husbands, engaging men in cervical cancer awareness programs, and screening facilities in close proximity to women's residences increases the uptake of cervical smear screening.…”
Section: Discussionmentioning
confidence: 99%
“…In the Nepali context, illiteracy, inadequate access to health care, and a trend toward accessing health care for curative rather than preventive purposes could explain the low uptake of cervical smear testing [8,19]. Other studies [20,21] have also shown that support from husbands, engaging men in cervical cancer awareness programs, and screening facilities in close proximity to women's residences increases the uptake of cervical smear screening.…”
Section: Discussionmentioning
confidence: 99%
“…Studies over the past two decades show that women are sometimes constrained by gender norms that limit their decision making power, and several recent studies echoed these ideas in various settings [6870]. Studies have highlighted men’s avoidance of help-seeking behaviors as a strategy to demonstrate their masculinity [71].…”
Section: Gender and Health Behaviorsmentioning
confidence: 99%
“…Furthermore, this integration of cervical cancer screening services will provide an important opportunity to engage male partners to educate them, particularly in counties where men have the dominant role for health care decision [1,9].…”
Section: Resultsmentioning
confidence: 99%